Implementasi Tugas dan Fungsi Kepala Sekolah pada TK di Desa Cimekar Kabupaten Bandung - Devita Nurul Fatimah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This study aims to identify the implementation of the duties and functions of school principals in two kindergarten institutions in Cimekar village, Bandung district and to identify supporting and inhibiting factors in carrying out their duties and functions as school principals. The data analysis techniques used are data reduction, data presentation, and drawing conclusions.The results of the research obtained are: (1) The principal in the first location has carried out his duties and functions as educators, administrators, supervisors, and motivators. However, the duties and functions of the principal as a manager, in facilities management, a leader in the vision and mission are not in accordance with the characteristics, and as an innovator, in carrying out their duties and functions to the fullest. Meanwhile, the principal in the second location has implemented and functions as an educator, manager, administrator, supervisor, leader, innovator, and motivator. The duties and functions of the principal can affect the quality of school education. (2) The supporting factor in carrying out the duties and functions of the principal at the second institution, namely the principal has created a school atmosphere that is mutual cooperation and kinship, resulting in a positive impact in a job. Abstrak. Penelitian ini bertujuan untuk mengidentifikasi implementasi tugas dan fungsi kepala sekolah pada dua lembaga TK di desa Cimekar kabupaten Bandung dan mengidentifikasi faktor pendukung dan penghambat dalam menjalankan tugas dan fungsi sebagai kepala sekolah. Adapun teknik analisis data yang digunakan yaitu, reduksi data, penyajian data, dan menarik kesimpulan. Hasil dari penelitian yang didapatkan adalah: (1) Kepala sekolah pada lokasi pertama telah melaksanakan tugas dan fungsi sebagai educator, administrator, supervisor, dan motivator. Namun tugas dan fungsi kepala sekolah sebagai manajer, dalam manajemen sarana prasarana, leader dalam merumuskan visi dan misi belum sesuai dengan karakteristik, dan sebagai inovator, dalam melakukan pembaharuan belum menjalankan tugas dan fungsinya secara maksimal. Sementara kepala sekolah pada lokasi kedua telah melaksanakan tugas dan fungsinya sebagai educator, manajer, administrator, supervisor, leader, inovator, dan motivator. Tugas dan fungsi kepala sekolah dapat berpengaruh terhadapat mutu pendidikan sekolah. (2) Faktor pendukung dalam menjalankan tugas dan fungsi kepala sekolah pada kedua lembaga tersebut yaitu kepala sekolah telah menciptakan suasana sekolah yang bersifat gotong royong dan kekeluargaan, sehingga menghasilkan dampak positif dalam suatu pekerjaan.